2022
DOI: 10.3390/su14063490
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy, External Shocks and Economic Growth Dynamics in East Africa: An S-VAR Model

Abstract: Resulting from the incessant political and economic uncertainty that bedevils the EAC region in the recent past, the various governments have used monetary policy changes in response to shocks from macroeconomic variables. However, the available literature shows a non-agreement by scholars as far as the dynamics in monetary policy, external shocks and macroeconomic activity connections are concerned, for both country-by-country analyses and regional assessments. This article widens the frontiers of knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…The result of the structured VAR and descriptive analysis by Chuku and Simpasa (2018) revealed a heterogeneous relationship between commodity product shocks and economic activities of the countries under investigation, while shedding more light on the nexus between commodity price fluctuations in some commodity-dependent African countries. The work by Olamide et al (2022) in Nigeria, which used the S-VAR estimate technique, was in line with this. The study found that oil price shocks had a large and negative impact on output and growth.…”
Section: Literature Reviewmentioning
confidence: 57%
See 2 more Smart Citations
“…The result of the structured VAR and descriptive analysis by Chuku and Simpasa (2018) revealed a heterogeneous relationship between commodity product shocks and economic activities of the countries under investigation, while shedding more light on the nexus between commodity price fluctuations in some commodity-dependent African countries. The work by Olamide et al (2022) in Nigeria, which used the S-VAR estimate technique, was in line with this. The study found that oil price shocks had a large and negative impact on output and growth.…”
Section: Literature Reviewmentioning
confidence: 57%
“…The existing association balance of payment (BOP), growth rate of gross domestic product (GDP GR), supply of money and inflationary rate were also explained contemporaneously in coefficients 𝑏 53 0 , 𝑏 54 0 and 𝑏 56 0 . The assumption that inflation responded contemporaneously to shocks in output adhered to the studies by (Olamide et al, 2022). The instantaneous response to oil and commodity prices, exchange rates and the rate of inflation by supply of money was explained in the sixth equation.…”
Section: Identification Of the Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Wen et al (2022) adopted the cross-sectional augmented ARDL (CS-ARDL) and the AMG methods to conclude that volatility in resource rents promotes long-term economic growth in BRICS countries. By adopting a structural vector autoregressive (S-VAR) model, Olamide et al (2022) reported that the economic dependence between East African countries implies that shocks to commodity prices will significantly and positively affect their economies. Zhang et al (2022) showed by using the fully modified OLS (FMOLS), DOLS, and canonical cointegrating regression (CCR), that natural resources volatility adversely and critically impacted global economic growth.…”
Section: The Economic Growth-natural Resources Nexusmentioning
confidence: 99%
“…The eight-week-long lockdowns implemented in 32 African countries prohibited all forms of social gatherings or functions, including public transport operations, schools, workplaces and markets, from opening. The closure of businesses came with the most economic impact, considering the size of the informal market in sub-Saharan Africa and the fact that many households depend on a daily income system (Olamide et al, 2022;Teachout & Zipfel, 2020;Zvokuomba & Kabonga, 2021). The freezing of formal business activities greatly impacted even those who do not depend on the daily income system.…”
Section: Economic Shocks Poverty and Au-eu Relationsmentioning
confidence: 99%